Исследование спектральных характеристик одиночных листьев растений; Известия вузов. Физика; Т. 55, № 6-2 - Яковлев А. Н. Алексей Николаевич; Козырева И. Н. Ирина Николаевна; Степанов С. А. Сергей Александрович; Туранов С. Б. Сергей Борисович; Кругликова Л. Л. Людмила Леонидовна (2012, 2012)
Заглавие с экрана